Effects of Sulfur Components on Crossing Point Temperature of Coal - Qi, Xuyao; Wang, Deming; Xin, Haihui; Qi, Guansheng (Asian Journal of Chemistry, 2013)
The crossing point temperature of initial and blended dried coal samples were tested. The weight percentages of FeS2 in blended coal samples were 3, 5 and 7 %. 50 g of coal particles ranging from 0.18 mm to 0.38 mm in size were put into a coal vessel attached at the center of oven. The temperature program increased the temperature at a rate of 0.8 ºC/min. Dry-air was permitted to flow into the coal vessel at different rates. The results indicate that the effects of sulfur components depend on reaction conditions and coal ranks. The reactivity of sulfur components in the coal is low under dry and low temperature conditions. These components form a film that covers the coal surface and slightly inhibits the self-heating of the coal. The inhibition degrees are different for different ranks of coal, which is due to the types and amount of active groups. It is usually more obvious for lower ranks of coal.